Keputusan Administrasi Negara (Beschikking) - Erliyana, Anna (LAW REVIEW, 2005)
Adiministrative decision made by government, legally called administrative Decree  (Ketetapan Aministrasi), is a decision issued by the authority in order to give legal basis  for all administrative actions of public agencies. Not only that, such Decree is also the  rules of procedure or code of conduct upon which every state of government agencies  conduct their interrelation and cooperation. The competence vested within its organs  agencies, which in turn also serves as the source of law for those agencies to operate. A  Decree issued by an Agency not given the legal authority is considered invalid that is,  null and void.